ECOLOGICAL EDUCATION: ITS ROLE AND SIGNIFICANCE IN THE MODERN EDUCATION SYSTEM - Norova Nafisa Farkhodovna (Web of Journals Publishing, 2025)
This article analyzes the significance of ecological education, methods for its effective implementation in the education system, and the expected outcomes. Ecological education is considered a process aimed at shaping individuals' ecological culture, fostering a harmonious relationship with nature, and promoting environmental protection. The study explores both the theoretical and practical aspects of ecological education, focusing on strategies for developing ecological consciousness and sustainable development principles. Additionally, the article highlights prospects for advancing ecological education through ecological projects, teacher training, collaboration with international organizations, and the integration of digital technologies.
Keywords: Ecological education, ecological upbringing, sustainable development, ecological culture, environmental protection, ecological awareness, ecological projects, innovative methods, education system, international cooperation.